Study of complete interconnect reliability for a GaAs MMIC power amplifier. Issue 5 (4th May 2018) - Lin, Qian; Wu, Haifeng; Chen, Shan-ji; Jia, Guoqing; Jiang, Wei; Chen, Chao
ABSTRACT: By combining the finite element analysis (FEA) and artificial neural network (ANN) technique, the complete prediction of interconnect reliability for a monolithic microwave integrated circuit (MMIC) power amplifier (PA) at the both of direct current (DC) and alternating current (AC) operation conditions is achieved effectively in this article. As a example, a MMIC PA is modelled to study the electromigration failure of interconnect. This is the first time to study the interconnect reliability for an MMIC PA at the conditions of DC and AC operation simultaneously. By training the data from FEA, a high accuracy ANN model for PA reliability is constructed. Then, basing on the reliability database which is obtained from the ANN model, it can give important guidance for improving the reliability design for IC.